2016
DOI: 10.3348/kjr.2016.17.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Arthroplasty: An Imaging Overview

Abstract: With advances in implant technology, total ankle arthroplasty (TAA) has become an increasingly popular alternative to arthrodesis for the management of end-stage ankle arthritis. However, reports in the literature do not focus on the imaging features of TAA. Through a literature review, we demonstrate basic design features of the current ankle arthroplasty system, and the normal and abnormal postoperative imaging features associated with such devices. Pre- and postoperative evaluations of ankle arthroplasty ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…It is important to note that medium-term follow-up of fixed-bearing and mobilebearing implants revealed no differences in functional tests or outcomes (5,6,(16)(17)(18)(19) . Patient satisfaction increased from 10% and 65% (in patients with first-and second-generation implants, respectively) to almost 90% with third-generation implants such as the HINTEGRA TAA (3,13,18,(20)(21)(22)(23)(24) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that medium-term follow-up of fixed-bearing and mobilebearing implants revealed no differences in functional tests or outcomes (5,6,(16)(17)(18)(19) . Patient satisfaction increased from 10% and 65% (in patients with first-and second-generation implants, respectively) to almost 90% with third-generation implants such as the HINTEGRA TAA (3,13,18,(20)(21)(22)(23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…Hintermann and colleagues described radiographic criteria for loosening of the implant: The tibial component should be considered loose if either its position has changed by more than 2° relative to the long axis of the tibia, or a progressive radiolucency of more than 2mm is detected around the implant on anteroposterior or lateral views. The criteria for a loose talar component are: subsidence greater than 5 mm or a change in position of more than 5° relative to the hindfoot axis (3,13,21) . Other studies have suggested possible implant loosening when components moved more than 5° or 5 mm in serial X-ray imaging (27)(28)33) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…97 Subsequent studies are performed with AP and lateral weightbearing technique depending on patient tolerance, and some institutions include lateral non-weightbearing maximally dorsiflexed and plantarflexed images to assess the range of motion. 98 The subsequent studies are used to evaluate for signs of osteointegration, determine osseous and prosthetic component alignment, and detect developing heterotopic ossification, in addition to evaluating range of motion.…”
Section: Imaging Strategymentioning
confidence: 99%
“…Additionally, MRI may help assess adjacent soft tissue structures, such as the surrounding ligaments and tendons. 98 As with CT, MRI of metallic devices can produce significant artifacts that limit its ability to characterize the adjacent bone and soft tissues, and several techniques have been used to reduce the degree of artifact to detect areas of expansile periprosthetic osteolysis. These include orienting the long axis of the device along the long axis of the main magnetic field, imaging on lower field-strength magnets with strong gradients, using high bandwidth sequences, substituting short tau inversion recovery sequences for chemically selective, fat-suppressed, fluid-sensitive sequences, and using thin section imaging.…”
Section: Imaging Strategymentioning
confidence: 99%